Pengesahan Perjanjian Kredit Jual Beli Rumah Oleh Notaris Yang Bukan Pembentuk Surat Pernyataan - Saputro, Joko; Putra, Mohamad Fajri Mekka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Notary are required to report irregularities. Notary in real world situations. It also has the power specified in Article 15 Paragraph 2 of Law no. 30 of 2004 concerning the change in the status of a notary through the second year of the Law. Based on Law No. 2 of 2014, his name was changed to Notary, after a regulation to verify and legalize. In a contract, especially in the banking industry credit agreement. Notary are often “protective letters” or closing letters, without the original deed arrangement and other powers under Article 15. The fact that notary often issue protection letters is due to the fact that they are not always clear. His work focuses on safety and the ability to produce accurate certifications. This is to create a cover letter to support bank loans. And indeed a notary who issues a cover note for a bank or a covernote to complete a credit agreement is no longer involved in the creation. Credit agreement, in other words, the bank has ordered a notary that is different from the notarial deed. Cover sheet maker again. From the results of these activities, the authors draw conclusions first. When ordering a notary, which notary is used by each party. Based on the agreement, the parties can choose which notary is used in the formation of a notarial deed. The bank ordered another notary in the process according to the author's information to sign a loan agreement for smooth banking processes at the bank